A memória histórica educativa do Orfanato Jesus Maria José na cidade de Juazeiro do Norte: 100 anos de permanências e rupturas (1916 A 2016) - Goiana, Ivaneide Severo (2016)
The present study consists of the investigation of the educational historical memory of the Jesus Maria Jose Orphanage, located in the city of Juazeiro do Norte, CE, where we seek to locate the transformations imposed by time, in relation to educational practices, its structure and functioning, In a comparative way with the socially surrounding ideas of welcoming poor or helpless childhood, nationally and internationally, in the period from 1916 to 2016. An institution designed by Father Cícero Romão Batista, with the purpose of gathering and educating Poor or "helpless" orphan girls. The initiating institution was coordinated by the Beatas of Juazeiro from 1916 to 1935, when they assumed the Daughters of St. Teresa of Jesus, remaining until the present day, completing (100) one hundred years of existence. We seek to problematize the hundred years of its existence, emphasizing the permanences and ruptures, in its historical educational process during this period. For this, we list the categories History of educational institutions, History of women in educational action, History of poor or "helpless" childhood. The methodology was based on qualitative research, supported by bibliographic, documentary and oral history studies. It was used the unstructured interview, with agents participating in the project including the subjects of the present time. Through the studies and the interviews carried out, we perceive some ruptures and permanences, both in the structural process and in the actions developed by its administrators. Of the ruptures, we emphasize three moments: The change of the Beatas in 1935 for the Daughters of Santa Teresa de Jesus; The installation of a Primary School in a room of the Orphanage, with the sisters having to adapt to a new educational methodology; When the school was closed, becoming the boarding school institution, becoming a philanthropic institution for welfare purposes, serving both sexes. During this process one can perceive changes, also in the educational process, according to the social transformations. We realize that the institution still has aspects of its idealization; the institution continues to focus on the educational process, with projects focused on the needy population, from its idealization to the present day, which we characterize as historical permanences that have resisted for a century.